Medication Reconciliation and Review Among Pharmacists in Kirkuk Province Iraq a Kap Study (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Medication reconciliation and review are essential processes to ensure medication safety, particularly during transitions of care. Despite their proven effectiveness in reducing adverse drug events, variability in implementation persists across healthcare settings. To assess pharmacists’ knowledge, attitudes, practices, and perceived barriers regarding medication reconciliation and review in various healthcare institutions. A cross-sectional survey was conducted among 155 pharmacists working in different healthcare sectors. The questionnaire included demographic data, knowledge-based multiple-choice questions, attitudinal Likert-scale items, and frequency-based practice assessments. Descriptive statistics, medians, and interquartile ranges (IQR) were calculated, and findings were compared with current literature. Participants demonstrated strong positive attitudes toward medication reconciliation and review, with all attitudinal statements yielding a median response of "Strongly Agree" (score = 5; IQR = 2). However, knowledge scores varied; only 44.5% correctly identified the primary purpose of medication reconciliation, and just 29.6% recognized the essential procedural steps. While 54.2% reported always performing reconciliation, the median practice score for medication review was lower (score = 3), indicating inconsistent implementation. Furthermore, 41.3% of participants experienced two concurrent barriers, with time constraints and lack of interprofessional collaboration frequently cited. Although pharmacists generally value medication reconciliation and review, significant gaps in procedural knowledge and consistency of practice remain. Targeted educational interventions, workflow integration, and institutional support are necessary to strengthen the effective implementation of these safety-critical processes.